Oskrbne funkcije v organizaciji mestnega prostora - na primeru Maribora - Pak, Mirko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
Trade is one of the most dynamic, sensitive and complex factor of use and organisation of urban areas. These are the basic questions discussed in this study about the regional centre of Maribor. Shooping centres are strengthening their role of holders of the procedure, having decisive influence not only on functional but also on overall development of town centre.
Keywords: Maribor; urbana geografija; mestni predeli; funkcije; oskrba; trgovina na drobno; trgovski centri